Legal Protection in the Indonesian Insurance Industry: A Comprehensive Analysis - Shaila Aulia Prilini; Fitrah Ardiansyah; Aulia Pratama; Dinda Seplinar Batubara; Annisa Larasati (ISNU Nine-Star Multidisciplinary Journal, 2025)
The development of the insurance industry in Indonesia demands a strong and effective legal system to protect the interests of all parties, including insurance companies, insureds, and regulators. However, there are still challenges in the implementation of basic insurance legal principles, such as the principles of good faith, indemnity, subrogation, and contribution, so a comprehensive study of the theoretical foundations, regulations, and practices in the field is needed. This study aims to analyze insurance law in Indonesia comprehensively, by assessing the suitability of theory, regulation, and implementation. The method used is normative legal research, which focuses on the study of laws and regulations, legal doctrine, and case analysis to assess the application of law in practice. This study covers Law Number 40 of 2014 concerning Insurance and its implementing regulations, including the Financial Services Authority (POJK) regulations. The results show that although regulations have provided a clear legal framework, there are a number of obstacles in implementation, such as lack of understanding of the insured, complex administrative practices, and limited oversight. This study concludes that the harmonization between insurance legal principles, regulations, and practices needs to be strengthened to ensure optimal legal protection, while encouraging the operational effectiveness of the insurance industry in Indonesia.